2013
DOI: 10.3233/ch-131781
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized blood better preserves cellular energy charge and vascular functions of intraoperatively stored saphenous vein grafts in comparison to isotonic sodium-chloride-solution

Abstract: OBJECTIVE: Several studies have addressed the optimal storage conditions for vascular grafts during surgery. The results remain contradictionary. This may be attributed to the fact, that the various vascular beds have a different sensitivity to storage. We analyzed the impact of storage in isotonic saline solution (NaCl) or heparinized blood the vascular functions of human saphenous vein grafts. Special care was taken to choose storage conditions which are relevant for intraoperative storage of a saphenous vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
1
24
0
8
Order By: Relevance
“…Endothelial integrity preventing early and late graft failure is critical for SVG function 3,7 . Several intraoperative factors, such as vessel harvesting technique, manipulation, and mechanical distension of venous grafts, quality of target vessel and exposure to high arterial pressures and turbulent flow have been accused to impair endothelial integrity thus triggering graft failure 1,9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelial integrity preventing early and late graft failure is critical for SVG function 3,7 . Several intraoperative factors, such as vessel harvesting technique, manipulation, and mechanical distension of venous grafts, quality of target vessel and exposure to high arterial pressures and turbulent flow have been accused to impair endothelial integrity thus triggering graft failure 1,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is no consensus concerning the optimal storage solution in daily practice, the choice of which is subjected to the surgeon and widely varies between different patients 1,7 . The most frequently used storage solution is NS/PSS (sodium chloride [0.9% NaCl]) 3 . Alternative storage solutions commonly used in cardiac surgery include, autologous heparinized blood (AHB), histidine‐tryptophan‐ketoglutarate, RL, University of Wisconsin solution (UWS), GALA solution (glutathione, ascorbic acid, l ‐arginine) and other solutions containing ions for pH buffering, antioxidants, high‐molecular‐weight molecules, and an ionic composition similar to that of intracellular fluid 3,5,7,9,15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four other studies failed to find any significant superiority of AHB over saline in preserving graft function. More recently, Wilbring et al reported that AHB preserves vascular contractile and endothelial functions of the SVG. Storage in NS rapidly compromises vascular functions and impairs cellular energy.…”
Section: Optimized Preservation Solutionsmentioning
confidence: 99%